Exosomes: Biological Pharmaceutical Nanovectors for Theranostics - Thomas, Shindu C.; Kim, Jin-Woo; Pauletti, Giovanni M.; Hassett, Daniel J.; Kotagiri, Nalinikanth (Frontiers in Bioengineering and Biotechnology, 2022)
Exosomes are natural cell-derived nanovesicles of endocytic origin that enable cellular crosstalk by transferring encapsulated molecular cargos across biological barriers, thereby holding significantly complex implications in the etiology and progression of diverse disease states. Consequently, the development of exosomes-based nano-theranostic strategies has received immense consideration for advancing therapeutic interventions and disease prognosis. Their favorable biopharmaceutical properties make exosomes a unique nanoparticulate carrier for pharmaceutical drug delivery. This review provides an update on the contemporary strategies utilizing exosomes for theranostic applications in nanomedicine. In addition, we provide a synopsis of exosomal features and insights into strategic modifications that control it’s in vivo biodistribution. We further discuss their opportunities, merits and pitfalls for cell/tissue targeted drug delivery in personalized nanotherapy.